Symptomatic Hemorrhagic Complications in Clot Lysis: Evaluation of Accelerated Resolution of Intraventricular Hemorrhage Phase III Clinical Trial (CLEAR III): A Posthoc Root-Cause Analysis. Issue 6 (23rd December 2017) - Fam, Maged D; Stadnik, Agnieszka; Zeineddine, Hussein A; Girard, Romuald; Mayo, Steven; Dlugash, Rachel; McBee, Nichol; Lane, Karen; Mould, W Andrew; Ziai, Wendy; Hanley, Daniel; Awad, Issam A
Abstract: BACKGROUND: As intraventricular thrombolysis for intraventricular hemorrhage (IVH) has developed over the last 2 decades, hemorrhagic complications have remained a concern despite general validation of its safety in controlled trials in the Clot Lysis: Evaluation of Accelerated Resolution of Intraventricular Hemorrhage Phase III (CLEAR-IVH) program. OBJECTIVE: To analyze factors associated with symptomatic bleeding following IVH with and without thrombolysis in conjunction with the recently completed CLEAR III trial. METHODS: We reviewed safety reports on symptomatic bleeding events reported during the first year after randomization among subjects enrolled in the CLEAR III trial. Clinical and imaging data were retrieved through the trial database as part of ongoing quality and safety monitoring. A posthoc root-cause analysis was performed to identify potential factors predisposing to rebleeding in each case. Cases were classified according to onset of rebleeding (during dosing, early after dosing and delayed), the pattern of bleeding, and treatment rendered (alteplase vs saline). RESULTS: Twenty subjects developed a secondary symptomatic intracranial hemorrhage constituting 4% of subjects. Symptomatic rebleeding events occurred during the dosing protocol (n = 9, 67% alteplase), early after the protocol (n = 5, 40% alteplase), and late (n = 6, 0% alteplase). Catheter-related hemorrhages were the most common (n = 7, 35%) followed by expansion or new intraventricular (n = 6, 30%) and intracerebral (n = 5, 25%) hemorrhages. Symptomatic hemorrhages during therapy resulted from a combination of treatment- and patient-related factors and were at most partially attributable to alteplase. Rebleeding after the dosing protocol primarily reflected patients' risk factors. CONCLUSION: Intraventricular thrombolysis marginally increases the overall risk of symptomatic hemorrhagic complications after IVH, and only during the treatment phase.